PENGARUH ELECTICAL STIMULATION, SACCADES DAN PURSUITS EXERCISE PADA DIPLOPIA MONOCULAR SINISTRA DI RSUD WONOSARI: CASE REPORT - Novendra Adhi Permana; Wahyuni Wahyuni; Ismadi Ismadi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduction: Diplopia is a visual disorder in which a person sees two images of one object. This case is a neurological case caused by lesions on nerve III (Oculomotor nerve), nerve IV (Trochlear nerve), and nerve VI (Abducens nerve). The purpose of this study was to determine the effect of giving electrical stimulation, saccades exercise and pursuits exercise in cases of left monocular diplopia. The method used in this study was a case study conducted on a 44-year-old female patient with left monocular diplopia. The interventions provided such as electrical stimulation, saccades exercise and pursuits exercise were carried out 2x a week and this study was conducted for 3 weeks. After 6x interventions, the results showed a decrease in the degree of pain and an increase in functional eye movement. In future research, it is hoped that there will be research with a long enough period of time so that it can determine the effectiveness of saccades exercise and pursuits exercise in increasing visual ability.